2007
DOI: 10.1016/j.jneuroim.2007.07.026
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1 suppresses T cell infiltration and VP2 puff B mutation enhances apoptosis in acute polioencephalitis induced by Theiler's virus

Abstract: GDVII and DA strains of Theiler's murine encephalomyelitis virus (TMEV) differ in VP2 puff B. One week after GDVII virus infection, SJL/J mice had large numbers of TUNEL + apoptotic cells with a relative lack of T cell infiltration in the brain. DA viruses with mutation in puff B induced higher levels of apoptosis than wild-type DA virus, but levels of inflammation in brains were similar between DA and DA virus mutants. The difference in inflammation among TMEVs could be due to TGF-β1 expression that was seen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 58 publications
2
28
0
Order By: Relevance
“…The GDVII strain induced low numbers of infiltrating T cells in SJL/J mice but high levels of neuronal apoptosis, and there was a negative correlation between apoptosis and perivascular inflammation. The DApBL2M mutant induced high numbers of infiltrating T cells and high levels of neuronal apoptosis, and there was a positive correlation between apoptosis and perivascular inflammation (22). Here we found that in C57BL/6 mice the DApBL2M mutant induced the highest number of PVC, for those TMEVs compared, in infected mice developing seizures by day 7 p.i.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…The GDVII strain induced low numbers of infiltrating T cells in SJL/J mice but high levels of neuronal apoptosis, and there was a negative correlation between apoptosis and perivascular inflammation. The DApBL2M mutant induced high numbers of infiltrating T cells and high levels of neuronal apoptosis, and there was a positive correlation between apoptosis and perivascular inflammation (22). Here we found that in C57BL/6 mice the DApBL2M mutant induced the highest number of PVC, for those TMEVs compared, in infected mice developing seizures by day 7 p.i.…”
Section: Discussionsupporting
confidence: 53%
“…Differences in neuropathology during the acute phase in SJL/J mice have been described for the DA strain of the TO group, the GDVII strain of the GDVII group, and the DApBL2M mutant (22). The DA strain induced high numbers of infiltrating T cells (perivascular inflammation) in SJL/J mice but low levels of neuronal apoptosis, with no correlation be- tween the two.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TMEV (86,96,97), porcine EMCV (17), and poliovirus (39) were reported to elicit apoptosis in certain cells of animals. It is not clear if these apoptotic events always developed as a direct consequence of viral reproduction in the target cells or if they were due to some secondary, e.g., immunological, reaction (52).…”
Section: Apoptosis-triggering and Apoptosis-preventing Functions Of Cmentioning
confidence: 99%
“…CD3 + T cells were visualized by antigen retrieval using citrate-based Vector ® Antigen Unmasking Solutions (Vector Laboratories, Burlingame, CA), followed by immunohistochemistry with anti-CD3 antibody (Dako, Carpinteria, CA), using the avidin-biotin-peroxidase complex (ABC) technique (Vector Laboratories) (42). The numbers of CD3 + cells were quantified under a light microscope using 10 to 12 transverse spinal cord segments per mouse as previously described (42).…”
Section: Methodsmentioning
confidence: 99%